Staging and management of feline chronic renal insufficiency - ADAMAMA-MORAITOU (Κ. Κ. ΑΔΑΜΑΜΑ-ΜΩΡΑΪΤΟΥ), K. K.; PARDALI (Δ. Σ. ΠΑΡΔΑΛΗ), D. (Journal of the Hellenic Veterinary Medical Society, 2017)
Feline chronic renal insufficiency (CRI) is a common clinical entity that is characterized by irreversible structural damage of the kidneys and subsequent loss of their functional capacity. It causes hemodynamic filtration and excretory failure of the kidneys, which leads to metabolic toxin accumulation and dysregulation of fluid, electrolyte and acid-base balance, as well as inability of the kidneys to excrete and respond to various hormones. Main laboratory findings of CRI are the increased concentration of urea and creatinine in serum. Serum creatinine is the principle factor for staging the disease. Four stages arerecognized. In addition, substaging uses two other diagnostic parameters, including borderline or severe proteinuria and/or systemic hypertension, which are considered among the risk factors of renal injury progression. These parameters determine therapy strategies and prognosis of the disease. Management is mainly conservative and is focused on improving the quality of the life of the cat, prolonging its life expectancy and preventing progression of renal damage. Hemodialysis and kidney transplantation are not feasible in our country, but, especially in cats, they are successfully performed in referral centres of USA and Europe. Dietary modification is considered the mainstay of treatment in cats with stable CRI. It is mainly based on restriction of protein, for reduction of their metabolic waste products in the body fluids, and phosphorus, in order to prevent renal secondary hyperparathyroidism. Adequate calorie intake is crucial in cats with CRI and it is achieved by increasing diet fat. Furthermore, clinical diets must be restricted in salt, in order to prevent systemic arterial hypertension. They must be supplemented with potassium, in order for hypokalemia to be amended, omega-3 polyansaturated fatty acids, which have been shown beneficial renal effects and fermendable fibers that serve as a nitrogen trap in the intestine. Moist food is preferred over dry food due to its partial contribution to the management of dehydration. It may be necessary to try several different diets before selecting the one the cat prefers or to apply various tricks in order to stimulate cat's appetite. The renoprotective action of angiotensin I converting enzyme (ACE) inhibitors is of mainly consideration. Apart from diet salt restriction, arterial hypertention can be managed by ACE inhibitors and/or calcium channel blockers administration; the latter is considered the antihypertensive therapy of choice. The first step in correcting hyperphosphatemia for the management of renal secondary hyperparathyroidism is the restriction of dietary phosphorus. However, this seems to be insufficient to normalize serum parathormone levels. The combination of intestinalphosphorus binding agents should be used and they are of proved efficacy in most cases. Among others, blood transfusion andrecombinant human erythropoietin administration may be needed in order for severe anemia to be managed. Potassium is supplemented if hypokalemia is evident, while alkalization therapy should be administered for metabolic acidosis. Prognosis is generally considered guarded to poor. Cats with stabilized renal function show substantially better short-term prognosis.